Analisis Meningkatnya Permohonan Dispensasi Kawin Masa Pandemi Covid 19 di Pengadilan Agama Padangsidimpuan dan Pengadilan Agama Panyabungan - Erna Ikawati; Darania Anisa (Palita: Journal of Social Religion Research, 2023)
Marriage Dispensation is an attempt by the prospective bride and groom to obtain a decision from the court to enter into a marriage for underage couples. Applications for marriage dispensation have increased since the COVID-19 pandemic hit Indonesia. This research focuses on analysing the factors behind the increase in requests for marriage dispensation and seeking efforts to overcome the increase in requests for dispensation. The research method used is field research with a qualitative approach. Data collection techniques were collected through observation and interviews with judges from the Padangsidimpuan Religious Court and the Pengabungan Religious Court. Interviews were also conducted with the Padangsidimpuan and Mandailing Natal Women's Empowerment and Child Protection Services and the people of Padangsidimpuan and Mandailing Natal, who submitted requests for dispensation from marriage. The results of this study indicate that the reasons for the prospective bride and groom applying for dispensation include juvenile delinquency (free sex), pregnancy out of wedlock, arranged marriages, low economy, and encouragement of traditional traditions (marlojong). Efforts were made to address the increase in requests for marital dispensation by strengthening the role and cooperation between the Religious Courts, the Women's Empowerment and Child Protection Service (DP3A), and the community (family)..